MALTODEXTRIN AND OILS IN THE DIET OF WEANED PIGLETS - Hauptli, L.; Berto, D. A. [UNESP]; Lo Tierzo, V. [UNESP]; Augusto, R. M. N. [UNESP]; Saleh, M. A. D. [UNESP]; Trindade Neto, M. A. (Inst Zootecnia, 2016)
The objective of this study was to evaluate the performance of piglets fed two sources of oil (soybean and palm oil) combined with maltodextrin and a blend of palm oil microencapsulated with maltodextrin, as well as the apparent digestibility coefficients of these diets. A total of 162 piglets weaned at 21 days, with a mean initial weight of 5.42 +/- 0.55 kg, were allocated in a randomized block design consisting of three treatments and 18 replicates of three animals each. The following treatments were evaluated: T1: diet containing soybean oil [3.03% in the pre-initial (I) and initial (II) diets] and maltodextrin (10.0% in I and 5.93% in II); T2: diet containing palm oil (3.03% in I and II) and maltodextrin (10.0% in I and 5.93% in II); T3: diet containing a blend of palm oil microencapsulated with maltodextrin (10.0% in I and II) and maltodextrin added to the blend (4.07% in I) so that the percentage of maltodextrin would be identical in the diets of the three treatments. The performance and digestibility data were submitted to analysis of variance using the MIXED and GLM procedures, respectively, of the SAS package and means were compared by the Tukey test (P< 0.05). Daily feed intake (DFI), average daily gain (ADG) and feed conversion (FC) were evaluated from 0 to 16 days and from 0 to 32 days postweaning. In the second week of the experiment, the apparent digestibility coefficients (ADC) of dry matter, crude protein and ether extract were measured by partial feces collection. No differences (P> 0.05) in DFI, ADG or FC were observed between piglets submitted to the different treatments. The ADC of dry matter was 4.25% lower (P< 0.05) for the diet containing palm oil microencapsulated with maltodextrin compared to the soybean oil diet. The ADC of ether extract was 54% higher (P< 0.05) in the soybean oil diet compared to the palm oil diet, which negatively affected the ether extract digestibility coefficient. In conclusion, palm oil microencapsulated or not with maltodextrin can replace soybean oil in the diets of weaned piglets without compromising their performance.
Keywords: performance; digestibility; palm oil; soybean oil; pigs